Fatty acid production by four strains of Mucor hiemalis grown in plant oil and soluble carbohydrates - Tauk-Tornisielo, Sâmia M. [UNESP]; Vieira, Joelma Maurício [UNESP]; Cecília, Maria [UNESP]; Carneiro, V. S. [UNESP]; Govone, José Silvio [UNESP] (My University, 2007)
Four Mucor hiemalis strains (M1, M2, M3 and M4), isolated from soil at a depth of 0 - 15 cm in the Juréia-Itatins Ecology Station (JIES), in the state of São Paulo, Brazil and were evaluated for the production of γ-linolenic (GLA) and other unsaturated fatty acids. Five growth variables (temperature, pH, carbon source, nitrogen source, and vegetable oils) were studied. Liquid media containing 2% vegetable oil (palm oil, canola oil, soybean oil, sesame oil, or sunflower oil) or 2% carbohydrate (fructose, galactose, glycerol, glucose, lactose, maltose, sucrose, sorbitol or xylose) and 1% yeast extract as a nitrogen source were used. The greatest biomass production was observed with M3 and M4 strains in palm oil (91.5 g l -1) and sunflower oil (68.3 g l -1) media, respectively. Strain M4 produced greater quantities of polyunsaturated acids in medium containing glucose. The GLA production in the M4 biomass was 1,132.2 mg l -1 in glucose medium. Plant oils were inhibitors of fatty acid production by these strains. © 2007 Academic Journals.
Keywords: γ-linolenic acid; Fatty acid production; Mucor hiemalis; Polyunsaturated acids; canola oil; carbohydrate; carbon; fatty acid; fructose; galactose; gamma linolenic acid; glucose; glycerol; lactose; maltose; natural product; nitrogen; palm oil; polyunsaturated fatty acid; sesame seed oil; sorbitol; soybean oil; sucrose; sunflower oil; unclassified drug; vegetable oil; xylose; biomass; Brazil; fatty acid synthesis; fungal strain; fungus growth; fungus isolation; Mucor; mucor hiemalis; nonhuman; pH; soil microflora; strain difference; temperature; Brassica napus var. napus; Glycine max; Helianthus; Sesamum indicum